HUBUNGAN KADAR KOLESTEROL DENGAN DERAJAT HIPERTENSI PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS HILIWETO GIDO, KABUPATEN NIAS - Melfa Vania Harefa; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Hypertension is one of the risk factors that increased cardiovascular disease. The prevalence of hypertension in Indonesia is 24% male and 22,6% female. One of the risk factors of hypertension is high blood cholesterol or hypercholesterolaemia, because high cholesterol cause of occlusion in the peripheral blood vessels that reduce the blood supply to the heart.This research aims to determine the relationship of cholesterol levels with hypertension degree in hypertensive patients in the work area of ​​PuskesmasHiliwetoGido. The population are the people who came to Puskesmas Hiliweto Gido, and sample are people who had blood pressure above normal and aged ≥18 years who came to Puskesmas Hiliweto Gido. The sample size is 135 people. This research is analytic with cross sectional study design, and continued with spearmen corelation and chi square analysis. From result show that the highest proportion of hypertensive patients were found in the age group ≥45 years (60%), women (67%), Protestant Christianity (89%), Nias (93%), primary education level (27% , working as farmer / laborer (35%), and married status (71%), hypercholesterolemia (58%) and hypertension group level 2 (40%). Based on statistical test analysis using Chi-Square test, p = 0,004 (p <0,05) means that there is significant correlation between cholesterol level and degree of hypertension Puskesmas parties need to promote to the public that it is important for every person to check blood pressure and cholesterol levels regularly to anticipate and prevent the occurrence of hypertension. Providing advice to the community, especially those suffering from hypertension to regulate healthy eating and lifestyle, and sugested to consume high fiber foods. Keywords: Hypertension, Cholesterol, Lifestyle, Nias